Assessment of the performance of selected irrigation schemes in Ethiopia - Ayana, M.; Awulachew, Seleshi Bekele (2009)
Unless attention is given to productivity improvements in food production, feeding the ever-increasing population persist to be the challenge for Ethiopia. The hope that irrigation development improves the productivity of agriculture, ensures food security, overcome impacts of rainfall variability and reduces poverty depends largely on how well the schemes are being operated and managed. This paper presents the results of performance assessments made in selected irrigation schemes in Ethiopia. For this purpose indicators that measure the water delivery and supply as well as output performances have been applied under data scarce situation. The conveyance efficiency in the main systems is found to be in the order of 58 - 89%. Generally the scheme level values of water supply performance indicators such as annual relative water supply (ARWS) and annual relative irrigation supply (ARIS) are equal to unity in Wonji irrigation scheme and greater than one in other schemes indicating that the water supplied exceeded the estimated demand. The values of water delivery ratio (WDR) varies between 0.62 (Wonji scheme) and 1.07 (Hare scheme). Scheme level values of water delivery and supply performance indicators revealed that there is no constraint of water availability at the scheme level. Schemes that produce sugar cane have higher outputs per units of water supplied and harvested area. On the contrary, community managed schemes showed low water productivity than that of large scale government agency managed schemes. As it is evidenced from the analysis of 59 irrigation schemes in the Awash river basin, schemes that use pump diversion have the opportunity to better control the water and sedimentation that enters the field. Pricing of irrigation water and the cost incurred in water conveyance were found to have a positive effect on the land and water resources of the irrigation schemes. Currently the direct water use fee is low to influence the demand and efficiency of water use. However, schemes which use pump diversion were found to consume less water and tended to expand land linearly with the increasing amount of diverted water. Low productivity of irrigated agriculture is possibly attributed to poor conditions of the irrigation infrastructure, inadequate management capacity and skills, lack of proper operation and on-farm water management skills and procedures, lack of incentives and hence low motivation to improve performance. Investment on these factors will have potentially significant impact in improving performance.